Microbial Leakage of Enterococcus Faecalis of Temporary Restorative Materials in Endodontic Treatment - Meneses Guzmán DDS, José Pablo; Loaiza Azofeifa DDS, MS, Evelyn (Odovtos - International Journal of Dental Sciences, 2015)
The aim of this study was to determine whether there is any significant difference in average days of Enterococcus faecalis microleakage through the coronal seal of four temporary restorative materials used in endodontics , Cavit® (3M), Duotemp® (Coltène), Clip® (VOCO) y Cimpat L.C® (Septodont). Ninety caries free extracted human premolars were randomly divided into 4 groups after the coronal access preparation; Group 1. Cavit® , Group 2 Duotemp® , Group 3. Clip , Group 4 Cimpat and controls were not restored with any material. Each group were mounted in 24 sterile well plates. Each well contained 2 ml of broth with bromocresol purple indicator 1% glucose. All Samples, except negative controls, were inoculated with E. faecalis in saline 0.85% 10 ^ 6 U / ml. The groups were observed daily for 30 days to detect changes in the indicator color from purple to yellow. ®. Jonckheere-Terpstra test was used with a 95% of confidence. The average days Filtration of materials was 12.50 for Clip®, 12.83 for Cavit®, 13.44 for DuoTemp® and 14.44 for Cimpat LC®. The temporary restorative materials studied shows microbial leakage after 15 days.